Effect of pipe corrosion product–goethite–on the formation of disinfection by-products during chlorination. Issue 2 (8th January 2016) - Hu, Chen-Yan; Zhang, Jing; Xu, Bin; Lin, Yi-Li; Zhang, Tian-Yang; Tian, Fu-Xiang
Abstract: The effect of goethite on the formation of disinfection by-products (DBPs) during chlorination was investigated under various reaction times, pH, and chlorine concentrations. The experimental results indicated that in the presence of goethite, the formation of DBPs was enhanced as pH and chlorine concentration increased. The enhancement of DBP formation could be attributed to the generation of hydroxyl radical ( ), which could oxidize natural organic matter (NOM) in water and produce more DBP precursors to react with chlorine. X-ray diffraction (XRD) and scanning electron microscope (SEM) analyses of goethite revealed that goethite may adsorb NOM on its surface and modify NOM structure. The reaction mechanisms of goethite-enhanced DBP formation were proposed in three steps: (1) the oxidation of NOM into small molecules available as DBP precursors by from the reaction between ferrous ions on goethite surface and chlorine; (2) the adsorption and modification of NOM on goethite surface responsible for increasing chlorine consumption; and (3) the presence of ferric ions on goethite surface promoted the formation of DBPs.